2019
DOI: 10.1016/j.joco.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness changes following cataract surgery in patients with type 2 diabetes mellitus

Abstract: Purpose To evaluate the choroidal thickness changes after cataract surgery in type 2 diabetic patients. Methods Three groups of patients were enrolled into this prospective study. Group A included diabetic patients without diabetic retinopathy (DR) or with mild non-proliferative diabetic retinopathy (NPDR) who underwent phacoemulsification, Group B included non-diabetic patients with significant cataract who underwent phacoemulsification, and Group C included diabetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…The choroid has the role of providing nutrition and oxygenation to the retinal pigment epithelium layer and the outer retina layer. The dysfunctional choroid also affects the retinal function and plays an important role in the development of DR [ 17 ]. Therefore, the use the retina and choroid parameters to observe fundus changes in diabetic patients after cataract surgery is more comprehensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choroid has the role of providing nutrition and oxygenation to the retinal pigment epithelium layer and the outer retina layer. The dysfunctional choroid also affects the retinal function and plays an important role in the development of DR [ 17 ]. Therefore, the use the retina and choroid parameters to observe fundus changes in diabetic patients after cataract surgery is more comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrahim et al [ 54 ], using EDI-OCT, found that SFCT was significantly increased 1 week after PE and returned to the preoperative level at month 3 after surgery. However, conflicting results have been reported in studies on postoperative SFCT changes in diabetic patients, with some studies showing that SFCT increased after PE surgery in diabetic patients [ 55 , 56 ], while others have found no change [ 57 , 58 ], and yet others have shown a postoperative reduction in choroidal thickness [ 17 ]. In the present study, the SFCT increased at week 1 after surgery in the PE group and began to decline at month 3, but did not return to preoperative levels until month 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most groups reported reduced CT in patients with diabetic retinopathy [26][27][28][29], and several groups reported that the choroid was thinner in eyes with diabetic macular edema (DME) [30][31][32]. Although some groups have reported CT after cataract surgery in patients with diabetes [33][34][35], the results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory mediators pass from anterior chamber, vitreous to retina and choroid leading to impairment of inner and outer blood retinal barrier causing an inflammatory cascade. 18,19 Another mechanism suggested for post-surgical inflammation is increased gene expression that simultaneously induces inflammatory response in all ocular layers. In a mouse model cataract surgery increased protein secretion in the retina and choroid due to expression of pro inflammatory gene related to chemokines such as CCL-2 and SDF-1, both of which can impair the blood-retinal barrier.…”
Section: Discussionmentioning
confidence: 99%